Triple Versus Double Therapy for the Treatment of Severe Infections Caused by Carbapenem-Resistant Enterobacteriaceae: A Systematic Review and Meta-Analysis - Wang, Lei; Tong, Xiang; Huang, Jizhen; Zhang, Li; Wang, Dongguang; Wu, Man; Liu, Tao; Fan, Hong (Frontiers in Pharmacology, 2020)
Introduction: The role of combination treatment in the management of carbapenem-resistant Enterobacteriaceae infections (CRE) is still unclear. There have been no meta-analysis comparing the efficiency of triple therapy in treating CRE infections with that of double therapy. In this perspective, we conducted a meta-analysis to clarify whether triple therapy is superior to double therapy in treating patients with CRE infections. Methods: We performed a systematic review, using PubMed and Embase without any restrictions until June 2019. Risk ratio (RR) with 95% CI were pooled to evaluate the effect of intervention. Results: A total of 32 studies were identified. Pooled analysis showed that triple therapy was not associated with a reduced mortality compared with double therapy (HR 1.07 95 % CI 0.91-1.25, P = 0.4). Conclusions: This meta-analysis suggests that double therapy is noninferior to triple therapy in the treatment of patients with CRE infections, although the quality of evidence in this systematic review is generally low based on current literatures.